Dark Chaucer: An Assortment - Seaman, Myra; Joy, Eileen A.; Masciandaro, Nicola (punctum books, 2012)
Although widely beloved for its playfulness and comic sensibility, Chaucer's poetry is also subtly shot through with dark moments that open into obscure and irresolvably haunting vistas, passages into which one might fall head-first and never reach the abyssal bottom, scenes and events where everything could possibly go horribly wrong or where everything that matters seems, if even momentarily, altogether and irretrievably lost. And then sometimes, things really do go wrong. Opting to dilate rather than cordon off this darkness, this volume assembles a variety of attempts to follow such moments into their folds of blackness and horror, to chart their endless sorrows and recursive gloom, and to take depth soundings in the darker recesses of the Chaucerian lakes in order to bring back palm- or bite-sized pieces (black jewels) of bitter Chaucer that could be shared with others . . . an "assortment," if you will. Not that this collection finds only emptiness and non-meaning in these caves and lakes. You never know what you will discover in the dark.